Projeto centrofauna, conservacionismo e sua extensão com os três setores da sociedade - Veiga, Nabor [UNESP]; Costa, Daniela Guimarães Alves da [UNESP]; Gonçalves, Stéfani [UNESP]; Silva, Cínthia Rio Branco da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Centrofauna Project "Screening Center of Wild Animals", authorized by the Brazilian Institute of Environment and Renewable Natural Resources (IBAMA) was created in 2002 with the purpose of receiving, triage, rehabilitate and allocate animals of our fauna and exotic wildlife, victims of environmental crimes. By involving various segments of society it is characterized as a university extension project. The main objectives are focused on the financial and operational sustainability of the center and the improvement of existing scientific techniques. To guarantee the economic and operational sustainability a partnership with the three sectors of society, governmental, private and nongovernment was made. Unesp, one of the government departments, in addition to technical design responsibility and improvement of existing techniques, works in environmental education of the people involved at all stages, from the receipt of the animals to their destination. The results obtained in these thirteen years of existence, show the effectiveness of the interrelation of the sectors and the improvement of techniques. It was concluded to date that this model is functional for the purpose of the project.

O Projeto Centrofauna, “Centro de Triagem de Animais Silvestres”, autorizado pelo Instituto Brasileiro do Meio Ambiente e dos Recursos Naturais Renováveis (IBAMA), foi criado em 2002 com a finalidade de receber, triar, reabilitar e destinar animais de nossa fauna e da fauna exótica, vítimas de crimes ambientais. Por envolver vários segmentos da sociedade caracteriza-se como um projeto de extensão universitária. Os principais objetivos estão voltados à sustentabilidade financeira e operacional do centro e ao aprimoramento das técnicas científicas existentes. Para a garantia da sustentabilidade econômica e operacional foi feita uma parceria com os três setores da sociedade, governamental, privado e não governamental. A Unesp, um dos setores governamentais, além da responsabilidade técnica do projeto e do aperfeiçoamento das técnicas existentes, atua na educação ambiental das pessoas envolvidas em todas as fases, desde o recebimento dos animais até sua destinação. Os resultados obtidos nesses treze anos de existência, revelam a eficácia da inter-relação dos setores e do aprimoramento das técnicas. Conclui-se até o presente momento que este modelo é funcional para o propósito do projeto.
Keywords: Wildlife; Environmental education; Extension; Vida silvestre; Educação ambiental; Extensão